The changing face of African literature = Les nouveaux visages de la littérature africaine (Cross/cultures ;, 2009)
The Changing Face of African Literature combines both the large picture ¿ a synopsis of current trends in African literature ¿ and the small: studies of individual texts and of themes across several texts. The large and the small are linked by recurring themes, such as gender and sexuality, the nation-state and its collapse, AIDS, war, and suffering.